A private wilderness : the journals of Sigurd F. Olson - Olson, Sigurd F., 1899-1982 (University of Minnesota Press, 2021)
The personal diaries of one of America's best-loved naturalists, revealing his difficult and inspiring path to finding his voice and becoming a writer. Few writers are as renowned for their eloquence about the natural world, its power and fragility, as Sigurd F. Olson (1899-1982). Before he could give expression to The Singing Wilderness, however, he had to find his own voice. It is this struggle, the painstaking and often simply painful process of becoming the writer and conservationist now familiar to us, that Olson documented in the journal entries gathered here. Written mostly during the years from 1930 to 1941, Olson's journals describe the dreams and frustrations of an aspiring writer honing his skills, pursuing recognition, and facing doubt while following the academic career that allowed him to live and work even as it consumed so much of his time. But even as he speaks with immediacy and intensity about the conditions of his apprenticeship, Olson can be seen developing the singular way of observing and depicting the natural world that would bring him fame-and also, more significantly, alert others to the urgent need to understand and protect that world. Author of Olson's definitive biography, editor David Backes brings a deep knowledge of the writer to these journals, providing critical context, commentary, and insights along the way. When Olson wrote, in the spring of 1941, "What I am afraid of now is that the world will blow up just as I am getting it organized to suit me," he could hardly have known how right he would prove to be. It is propitious that at our present moment, when the world seems once more balanced on the precipice, we have the words of Sigurd F. Olson to remind us of what matters-and of the hard work and the wonder that such a reckoning requires.